Anxiety disorders and GABA neurotransmission: a disturbance of modulation - Nuss P (Dove Medical Press, 2015)
Philippe Nuss1,21Department of Psychiatry, Hôpital St Antoine, AP-HP, 2UMR 7203, INSERM ERL 1057 – Bioactive Molecules Laboratory, Pierre and Marie Curie University, Paris, FranceAbstract: Lines of evidence coming from many branches of neuroscience indicate that anxiety disorders arise from a dysfunction in the modulation of brain circuits which regulate emotional responses to potentially threatening stimuli. The concept of anxiety disorders as a disturbance of emotional response regulation is a useful one as it allows anxiety to be explained in terms of a more general model of aberrant salience and also because it identifies avenues for developing psychological, behavioral, and pharmacological strategies for the treatment of anxiety disorder. These circuits involve bottom-up activity from the amygdala, indicating the presence of potentially threatening stimuli, and top-down control mechanisms originating in the prefrontal cortex, signaling the emotional salience of stimuli. Understanding the factors that control cortical mechanisms may open the way to identification of more effective cognitive behavioral strategies for managing anxiety disorders. The brain circuits in the amygdala are thought to comprise inhibitory networks of Υ-aminobutyric acid-ergic (GABAergic) interneurons and this neurotransmitter thus plays a key role in the modulation of anxiety responses both in the normal and pathological state. The presence of allosteric sites on the GABAA receptor allows the level of inhibition of neurons in the amygdala to be regulated with exquisite precision, and these sites are the molecular targets of the principal classes of anxiolytic drugs. Changes in the levels of endogenous modulators of these allosteric sites as well as changes in the subunit composition of the GABAA receptor may represent mechanisms whereby the level of neuronal inhibition is downregulated in pathological anxiety states. Neurosteroids are synthesized in the brain and act as allosteric modulators of the GABAA receptor. Since their synthesis is itself regulated by stress and by anxiogenic stimuli, targeting the neurosteroid-GABAA receptor axis represents an attractive target for the modulation of anxiety.Keywords: allosteric modulation, amygdala, salience, Υ-aminobutyric acid, neurosteroids